Case study research design and methods - Yin, Robert K. (Los Angeles SAGE, 2014)
Providing a complete portal to the world of case study research, the Fifth Edition of Robert K. Yin?s bestselling text offers comprehensive coverage of the design and use of the case study method as a valid research tool. The book offers a clear definition of the case study method as well as discussion of design and analysis techniques. The Fifth Edition has been updated with nine new case studies, three new appendices, seven tutorials presented at the end of relevant chapters, increased coverage of values and ethics, expanded discussion on logic models, a brief glossary, and completely updated citations. This book includes exemplary case studies drawn from a wide variety of academic fields.
Includes bibliographical references (pages 243-257) and index.
Keywords: Case method